Sistema automatizado de aquisição, em tempo real, de umidade e temperatura do solo na irrigação - Diniz, Anibal Mantovani (2017)
The modern agriculture is based on the application of techniques, methodologies and equipment that optimize their processes, thus increasing agricultural production, reducing costs and interfering less in nature. An important area of research in Agricultural Engineering is the development and use of equipment and sensors electronic to support increased agricultural productivity. This work presented a contribution to irrigation through the development and use of free software and hardware for direct measurements of soil moisture and temperature values during the plant cycle, thus allowing optimize the use of water in the process. In the system proposal, four moisture sensors were used, one resistive and three capacitive. The research was carried out in the laboratory and the soil used in the experiment was collected at the Experimental Nucleus of Agricultural Engineering of the State University of the West of Paraná. The soil was characterized as typical Distroferric Red Latosol and very clayey texture (66%). The soil was discarded and oven dried, then divided into 20 containers with addition of known water volumes in each. A network of Mesh-type sensors was developed to read and transmit data read to a single Gateway. The sensor node was designed and built with an Arduino Nano, NRF24L01 radio, capacitive sensors of type SHT20 and DHT22 in addition to FC-28 that is resistive. The system also featured a Real Time Clock DS1302, three photovoltaic cells and battery charger circuit. The Gateway circuit that connects the system to the internet was built with an Arduino Uno. Domoticz software was used to store the data and make it available on a server connected to the Internet. The data were obtained from the sensors placed in the containers and one of the results was the cubic modeling of the relationship between each of the sensors, the TDR and the greenhouse method. The values of the coefficient of statistical determination obtained show that the models that best explain the relation between the values obtained by the greenhouse method are the TDR and the resistive sensor, although the other sensors also presented a good coefficient of determination. The consumption of the sensor node board is 168 mW and the distance tested between devices up to 100 m showed that there was no loss of the data packet. The cost obtained from a node was R$ 251.00 and the Gateway R$ 115.00. The cost of a new TDR in Brazil of the model used in the experiment is R$ 176,000.00. Therefore, the analysis of the data presented showed the feasibility of using the sensors proposed in the network and resulted in a model to be applied for each device at a viable cost to the rural producer.